2022
DOI: 10.1002/pul2.12041
|View full text |Cite
|
Sign up to set email alerts
|

Plasma matrix metalloproteinase 2 is associated with severity and mortality in pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a life‐threatening disease characterized by vasoconstriction and remodeling of the pulmonary vessels. Risk stratification in PAH could potentially be improved by including novel biomarkers related to PAH pathobiology. We aimed to investigate the relationship between extracellular matrix (ECM)‐related proteins, survival, and European Society of Cardiology and European Respiratory Society (ESC/ERS) risk stratification scores in patients with PAH. Plasma samples and hemody… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…The findings of the recent research showed that the best cutoff point of MMP-2 to differentiate cases in PAH-CHD group from CHD group without PH was ≥ 109.7 ng/ml, with sensitivity of 52 %, specificity of 96%, PPV of 96 % and NPV of 52 %, which are in line with Arvidsson et al who revealed serum MMP-2 in PAH had sensitivity of 52% and specificity of 93% [37].…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…The findings of the recent research showed that the best cutoff point of MMP-2 to differentiate cases in PAH-CHD group from CHD group without PH was ≥ 109.7 ng/ml, with sensitivity of 52 %, specificity of 96%, PPV of 96 % and NPV of 52 %, which are in line with Arvidsson et al who revealed serum MMP-2 in PAH had sensitivity of 52% and specificity of 93% [37].…”
Section: Discussionsupporting
confidence: 71%
“…Arvidsson et al [37] and Tiede et al [38] revealed an increased risk of death among PH cases with MMP-2 concentrations above the median. This highlights the possible significance of MMP-2 as a prognostic indicator, as greater MMP-2 concentrations were related with a poor outcome in PAH.…”
Section: Discussionmentioning
confidence: 97%
“…Our prior work additionally demonstrated an association between increased post-operative MMP 7 and post-Stage 2 hypoxemia 5 . Increased circulating MMP 7 has also been associated with pulmonary pathology in a number of clinical populations, including idiopathic pulmonary fibrosis, chronic obstructive pulmonary disease, and pulmonary arterial hypertension 7 , 28 30 . In this context, our results suggest a role for increased MMP 7 exposure as both a biomarker of disease and a potential mechanistic driver of pulmonary vascular inadequacy in SVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Two additional biomarkers of interest, TIMP 4 and MMP 1, were directly associated with post-Stage 2 LOS. While the role of MMP 1 in the pulmonary vasculature is less clear, elevated TIMP 4 level has been previously identified as a biomarker of disease and indicator of poor prognosis in pulmonary arterial hypertension 30 , 32 34 . Although not evaluated previously in SVHD, a pediatric study linked elevated TIMP 4 levels to increased pulmonary vascular stiffness by MRI providing a potential mechanism linking TIMP 4 activity to impaired tolerance of Stage 2 physiology 20 .…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious that intracellular signal transduction is ubiquitous in the pathogenesis of PH in COPD [36] . Existing studies also show that ECM is implicated in the development of pulmonary vascular remodeling and high level of ECM-related proteins such as MMP-2 are associated with poor survival and prognosis of PH patients [37] . Additionally, release of calcium ions from the endoplasmic reticulum to the cytoplasm and mitochondria is an important mediators of cell proliferation, migration and mesenchymal transition, thereby affecting the contractility and resistance of pulmonary artery [38][39] .…”
Section: Discussionmentioning
confidence: 99%